Certain K0-Monoid Properties Preserved by Tracial Approximation - Qingzhai Fan (Abstract and Applied Analysis)
We show that the following K0-monoid properties of C*-algebras in the class Ω are inherited by simple unital C*-algebras in the class TAΩ: (1) pseudocancellation property, (2) weakly divisible, (3) strongly separative, (4) separative, and (5) preminimal.